Adolescents, music and music therapy : methods and techniques for clinicians, educators and students - McFerran, Katrina, 1972- (London ; Philadelphia : Jessica Kingsley Publishers, 2010)
The author presents an empowering approach to music therapy with adolescents that places the therapist in a collaborative relationship with the individual or group. A range of strategies are explored, including song sharing and improvisation.
Taking a systematic look at the literature -- The real deal on how to work with adolescents -- What is healthy adolescence and how does music help? -- Using existing songs -- Writing original songs -- Group improvisation -- Individual improvisations -- Community music therapy -- Four brief approaches to grief -- Preparing for performances.
Includes bibliographical references and indexes.
Keywords: Music therapy for teenagers; Teenagers -- Mental health